Green innovation for competitiveness: Impact on GDP growth in the European Union - Rūta Banelienė; Rolandas Strazdas; Cristina Blanco González-Tejero; Sorin Gavrila Gavrila (Contemporary Economics, 2023)
Since the start of the Industrial Revolution, the global climate has changed dramatically. Concentrations of greenhouse gases (GHGs) in the atmosphere have increased sharply, followed by an increase in global average temperatures. However, business activities related to environmental protection are mostly focused on the implementation of legal rules instead of voluntary initiatives such as green innovation due to doubts about costs and profit. The goal of this research is to identify the impact of green innovation on economic growth in an innovative environment and digitalization conditions by using sophisticated indexes and regression analysis. The results show that green innovations have a positive impact on economic growth in the European Union (EU). However, the impact of digitalization on economic growth is still under discussion and depends on qualitative aspects of coverage and how they are reflected in digitalization indicators. It is important to emphasize that the data of this empirical study only cover EU countries that are subject to EU regulation and have similar trends in the development and diffusion of green innovations. Non-EU countries may have different approaches and policies influencing the maturity and diffusion of green innovations. The results of this research provide a scientific basis for strategic planning at the national and business levels, encouraging a focus on the development of green innovation not only as a means of reducing the impact of climate change but also as a strategic direction for increasing competitiveness and economic growth.
Keywords: A10; C30; E17; F63; O30; O40; 330; green innovation; digitalization; GDP growth; European Union